2023
DOI: 10.1101/gad.350320.122
|View full text |Cite
|
Sign up to set email alerts
|

Localization ofKif1cmRNA to cell protrusions dictates binding partner specificity of the encoded protein

Abstract: Subcellular localization of messenger RNA (mRNA) is a widespread phenomenon that can impact the regulation and function of the encoded protein. In nonneuronal cells, specific mRNAs localize to cell protrusions, and proper mRNA localization is required for cell migration. However, the mechanisms by which mRNA localization regulates protein function in this setting remain unclear. Here, we examined the functional consequences of localization of the mRNA encoding KIF1C. KIF1C is a kinesin motor protein required f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Instead, most downregulated RNAs in KIF1C-KO axons were related to neurotransmission, the synaptic zone, and misfolded protein clearance. Since the previously mentioned investigations regarding KIF1C have been performed in other cell types (Wang et al ., 2017; Pichon et al ., 2021; Nagel et al ., 2022; Norris & Mendell, 2023), it is possible that KIF1C -dependent transport in CNs uses different motors, independent of APC. However, by which mechanism transport in CNs is conducted needs to be subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, most downregulated RNAs in KIF1C-KO axons were related to neurotransmission, the synaptic zone, and misfolded protein clearance. Since the previously mentioned investigations regarding KIF1C have been performed in other cell types (Wang et al ., 2017; Pichon et al ., 2021; Nagel et al ., 2022; Norris & Mendell, 2023), it is possible that KIF1C -dependent transport in CNs uses different motors, independent of APC. However, by which mechanism transport in CNs is conducted needs to be subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…KIF1C is implicated in many functions, including maintenance of Golgi morphology, cell migration, formation of podosomes in vascular smooth muscle cells and macrophages, and MHC presentation on the cell (Kopp et al ., 2006; del Rio et al ., 2012; Simpson et al ., 2012; Theisen et al ., 2012; Bhuwania et al ., 2014; Efimova et al ., 2014; Lee et al ., 2015). Interestingly, KIF1C has also been implicated in long range directional transport of APC-dependent mRNAs and RNA-dependent transport of the exon junction complex (EJC) into neurites, suggesting KIF1C can bind RNA in a direct or indirect manner (Pichon et al ., 2021; Nagel et al ., 2022; Norris & Mendell, 2023). However, which impact loss of KIF1C has on the axonal transcriptome remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…As a kinesin, what does LLPS activity mean for KIF1C's function? Recently, several groups reported that KIF1C associates with and transports mRNAs [43][44][45][46] . These findings are particularly interesting in light of KIF1C's ability to undergo LLPS, as many phase-separating proteins are known to be RNAbinding proteins (RBPs) 27,75 .…”
Section: Kif1c Condensates Enrich Rna and Facilitate Mrna Transport I...mentioning
confidence: 99%
“…9). First, endogenous KIF1C protein is localized diffusely throughout the cell and only a few small droplets are observed in the cell periphery 45,49 . Second, mRNAs whose localization at the cell periphery is dependent on KIF1C can be transported in the form of single copies and then coalesce into larger clusters once they reach their destination in cell protrusions 43,85 .…”
Section: Relationship Between Kif1c Llps and Mrna Transportmentioning
confidence: 99%
See 1 more Smart Citation